Pensamiento estratégico en la exportación de arroz colombiano (2020)
The purpose of this work is the application of strategic thinking in the export of rice through the habits of rice producers, their characteristics in terms of their way of thinking or rationing and the way they behave. For the development of a strategic thought in the export of rice, the characteristics of the product to be offered must be taken into account, to determine its prices, quality and added values that it will present compared to products with similar characteristics; the purpose of a strategic thought focused on the export of rice, must be to offer you better services, results and yields, for the part that offers the product as the one that buys it, that is why values, habits are of great importance or qualities that people present to determine the strategies that will be applied to fulfill the objectives, in a fairly short period of time.